THE SEMIOTIC CONSTRUCTION OF MEANING AND VALUE: CANTHIK KIAI RAJAMALA AS A SYMBOL IN THE CONTEMPORARY SOCIAL PERSPECTIVES - Dewi, Rosa Bila Putri; Putra, Hutomo; Bawono, Rochtri Agung; Wardi, I Nyoman (Paradigma: Jurnal Kajian Budaya, 2024)
Canthik Kiai Rajamala is one of the heirlooms owned by the Keraton Kasunanan Surakarta. There are two Canthik Kiai Rajamala, each stored in the Keraton Surakarta Museum and the Radya Pustaka Museum. Surakarta is the only region traversed by the Bengawan Solo River that possesses a canthik, making it a distinctive and unique cultural heritage for the people of Surakarta. This research addresses the issue of how the meaning and value construction of Canthik Kiai Rajamala can be interpreted through Pierce's semiotic triangle theory. Additionally, this study examines how contemporary Surakarta society perceives the Canthik Kiai Rajamala. The objective of this research is to identify the cultural meanings and values of Canthik Kiai Rajamala, which are preserved in the Keraton Surakarta Museum and the Radya Pustaka Museum. The interpretation of the object involves the community’s perspective on CanthikKiai Rajamala, from its creation and use to its current status as a museum artifact. This study also focuses on the local wisdom system of Surakarta society in interpreting the cultural traditions associated with Canthik Kiai Rajamala, and its relationship with the environment and local customary community.